MEMBANGUN KESADARAN RISIKO DIGITAL DAN TATA KELOLA TEKNOLOGI BAGI MAHASISWA DI ERA TRANSFORMASI DIGITAL - Farhatun Nisa; Citra Sukmadilaga; Moh. Wahyudin Zarkasyi; Srihadi Winarningsih (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid acceleration of digital transformation is compelling organisations to build greater awareness of technology governance and the risks it entails. Despite the fact that this group will occupy strategic roles in organizational governance practice in the years ahead, the understanding of IT governance and digital risk management remains relatively limited among accounting students. This community service activity aims to enhance the understanding of young members of the Indonesian Institute of Accountants (IAI) regarding technology governance and risk management in the context of digitalisation, delivered through a webinar on 23 May 2026. The activity was a collaboration between the Young Members of IAI West Java Region and the Doctoral Program in Accounting Sciences at Universitas Padjadjaran, with 87 active participants from 11 higher-education institutions. The program was designed using a participatory educational approach comprising three stages: preparation, implementation, and evaluation of the program. The effectiveness of the activity was measured using a Likert scale questionnaire (1–5) covering four aspects: material quality, presenter delivery, participant comprehension and webinar benefits. Evaluation results indicated very good ratings across all aspects, with an overall mean above 4.40 out of 5.00. The activity contributed to the development of participants' initial competencies in understanding IT governance frameworks, risk management processes based on ISO 31000:2018 and COSO, and awareness of digital risks within organisational contexts. Findings from the discussion session revealed participants' need for more applied understanding, particularly regarding the preparation of risk registers within organisations, indicating the need for more structured, continuing capacity-development programmes.